"From Knowledge to Action: Financial Literacy and Its Effect on Investment Decision-Making" (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The growing complexity of financial markets and investment opportunities demands that individuals be equipped with the necessary skills to make informed financial decisions. Financial literacy, the ability to understand and apply various financial concepts, is widely recognised as a crucial determinant of individuals financial behaviours, particularly investment decisions. This paper examines the relationship between financial literacy and investment behavior, focusing on how financial knowledge influences risk tolerance, portfolio diversification, and overall investment strategies. By analysing existing literature and employing both qualitative and quantitative research methods, this study offers valuable insights into the role of financial literacy in shaping investment decisions and its broader implications for financial education.